(untitled) (The Journal of Ad-din Women’s Medical College, 2023)
Primary ciliary dyskinesia (PCD) is a rare autosomal recessive genetic condition due to dysfunction of cilia, the microscopic organelles in child’s respiratory system. This results in defective functioning of cilia, leading to chronic sinu-pulmonary infection, situs inversus, dextrocardia, and congenital heart abnormalities, ultimately leading to subfertility and infertility. Alike other low-income countries, lack of awareness on PCD remains one of the existing challenges associated with PCD diagnosis, in Bangladesh (BD), particularly in its primary care-phase, since it’s non-specific symptoms mimic other conditions. Basically, absence of a single, “gold standard” genetic-based diagnostic test is fatefully missing in BD. The test in itself remain highly expensive and requires certain sophisticated steps, hi-fi equipment and a highly-trained professional team to run and maintain those appropriately. Although management predominantly remains supportive it is not based on high-level evidences, per se. This updated review aims to discourse the importance of early, accurate and available diagnosis of PCD and its management particularly in countries like BD where it is prevalent but often remains under-cover. The Journal of Ad-din Women’s Medical College; Vol. 11 (1), Jan 2023; p 44-50